Information System for Learning Control in Teaching Russian Sign Language: Process and Data Modeling - Logachev, Maxim; Chernova, Vera; Laamarti, Yuliya; Makhamatov, Tair; Ivlev, Vitaliy; Giulodori, Lucio; Tutkova, Irina (International Journal of Instruction, 2022)
The article describes project of the information system to control the teaching of Russian sign language. The aim of the conducted study is to consolidate existing algorithms and software tools to ensure the integrity, and objectivity in the implementation of professional training of specialists in the field of Russian sign language. The authors conducted a study of specialized sources in order to highlight the features of the subject area for the implementation of design processes. With the employment of structural analysis methods, a formal data model is obtained that describes the concept of a database that provides data storage and processing necessary for the full-scale operation of the information system. Using a combination of methods of structural analysis and object-oriented design, a model of the process of user interaction with the designed information system is obtained. The advantage of such a model is the selection of data objects necessary for the implementation of each stage of the process, as well as the objects obtained and available after their execution. All users of the system are classified according to the principle of data availability. The results obtained at the project stage in the future are the basis for the development of the corresponding software product.